Current Practices and Concerns of Teachers Integrating Lesbian and Gay Materials into the Composition Curriculum Or, What Are We Doing and How Are We Doing It? - Parmeter, Sarah-Hope. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
A number of teachers have for some years been creating lesbian and gay-inclusive college-level composition courses. Teachers who create such courses do so because it is intrinsic to their notion of good teaching, which includes the goal of fostering students' personal relationships with the written word. Many of these teachers often speak of themselves as role models. By virtue of the nearly complete absence of lesbian and gay voices from composition readers, any teacher wanting to create a lesbian and gay-inclusive course will have to do so through deliberate effort, supplying supplementary readings. Teachers thinking about developing such courses sometimes worry about the safety (in terms of job security) of taking on such work. Structure is crucial to creating effective lesbian and gay inclusive courses. Teachers need to have a clearly articulated purpose and plan, or the material can lead to volatile discussions and homophobic diatribes. There is a danger in a "neutral" curriculum. What might seem politically charged to one student is an essential matter of identity to another. "Neutral" courses will serve most poorly those students who are already most marginalized. (RS)
ERIC Note: Paper presented at the Annual Meeting of the Conference on College Composition and Communication (42nd, Boston, MA, March 21-23, 1991).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College English; College Faculty; Course Content; Higher Education; Homosexuality; Teacher Behavior; Teacher Role; Undergraduate Students; Writing (Composition); Writing Instruction; Writing Contexts; Speeches/Meeting Papers; Reports, Descriptive